Diagnosis and troubleshooting of automotive electrical, electronic, and computer systems - Halderman, James D., 1943- (Upper Saddle River, N.J. : Pearson Prentice Hall, 2010)
This volume presents an introduction to automotive electrical and engine performance topics. It is NATEF- and ASE-correlated and presents principles and practices of diagnosis and troubleshooting of automotive electrical, electronic, and computer. This textbook covers the material necessary for Automobile Electrical/Electronic Systems (A6) and Engine Performance (A8) areas of certification as specified by ASE and NATEF.
Service information, tools, and safety -- Environmental and hazardous materials -- Electrical fundamentals -- Electrical circuits and ohm's law -- Series circuits -- Parallel circuits -- Series-parallel circuits -- Digital meters -- Oscilloscopes and graphing multimeters -- Automotive wiring and wire repair -- Schematics and troubleshooting -- Capacitance and capacitors -- Magnetism and electromagnetism -- Electronic fundamentals -- Computer fundamentals -- Batteries -- Battery testing and service -- Cranking system -- Cranking system diagnosis and service -- Charging system -- Charging system diagnosis and service -- Lighting and signaling circuits -- Driver information and navigation systems -- Horn, wiper, and blower motor circuits -- Accessory circuits -- Airbag and pretensioner circuits -- Audio system operation and diagnosis -- Computer and network fundamentals -- On-board diagnosis -- Computer sensors -- Ignition system components and operation -- Ignition system diagnosis and service -- Fuel pumps, lines, and filters -- Fuel injection components and operation -- Fuel injection system diagnosis and service -- Vehicle emission standards and testing -- Emission control devices operation and diagnosis -- Scan tools and engine performance diagnosis -- Hybrid electric vehicle fundamentals -- Hybrid electric vehicle safety procedures -- Fuel cells and advanced technology -- Appendix 1: ASE test correlation chart: electrical/electronic systems -- Appendix 2: ASE test correlation chart: engine performance -- Appendix 3: NATEF task list correlation chart: electrical/electronic systems -- Appendix 4: NATEF task list correlation chart: engine performance.
Includes bibliographical references and index.
Keywords: Automobiles -- Electric equipment -- Maintenance and repair; Automobiles -- Electronic equipment -- Maintenance and repair; Automobiles -- Electric equipment -- Maintenance and repair; Automobiles -- Electronic equipment -- Maintenance and repair